2001
DOI: 10.1002/eej.1
|View full text |Cite
|
Sign up to set email alerts
|

Neutron production rate and plasma characteristics of spherically convergent beam fusion

Abstract: Experimental and simulation results of a spherical glow discharge for a portable neutron source are presented. The experimental device is a 45-cm-diameter, 31-cm-high stainless-steel cylindrical chamber, in which a spherical mesh-type anode 30 cm in diameter is installed. The spherical grid cathode consists of 2.0-mm-diameter stainlesssteel wire, which is made into an open spherical grid of 5-cm diameter. The system is maintained at a constant pressure of 1 to 15 mTorr by feeding hydrogen or deuterium gas. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Miley et al [5], who studied the breakdown voltage characteristics as a function of pressure-electrode separation (pd), using a spherical cathode grid mounted concentrically within a grounded spherical vacuum vessel, which served as the anode. Yamauchi et al [2], using a pulsed discharge confirmed, by experimental measurements and simulation calculations, that a virtual anode is formed in the central part inside the grid cathode in a spherical glow discharge for a portable neutron source. Popov et al [6] studied the electron energy distribution function and the temperature of the electron groups using a Langmuir single probe, in a dc discharge tube with coaxial electrodes, for argon plasma.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Miley et al [5], who studied the breakdown voltage characteristics as a function of pressure-electrode separation (pd), using a spherical cathode grid mounted concentrically within a grounded spherical vacuum vessel, which served as the anode. Yamauchi et al [2], using a pulsed discharge confirmed, by experimental measurements and simulation calculations, that a virtual anode is formed in the central part inside the grid cathode in a spherical glow discharge for a portable neutron source. Popov et al [6] studied the electron energy distribution function and the temperature of the electron groups using a Langmuir single probe, in a dc discharge tube with coaxial electrodes, for argon plasma.…”
Section: Introductionmentioning
confidence: 84%
“…When the virtual anode is formed, it causes recirculation for some of positive ions toward the grid cathode and decelerates more of ions to converge at the center; hence ion density is slightly decreased. After that ions are converged at the center from all directions, so the ion density is increased again until it reaches the center at r = 0 [2,7]. It is noticed from Figure 11 that values of ion density calculated using Poisson equation are different from and less than that obtained using the single and double probes.…”
Section: Electron Temperature and Plasma Densitymentioning
confidence: 91%
See 3 more Smart Citations